Analysis Of Operational Risk Using Loss Distribution Approach : A Study Of Epc Business - Tiara, Lydia; Prijadi, Ruslan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This abstract describes a comprehensive analysis of operational risks in engineering, procurement, and construction (EPC) business by using calculation of loss distribution approach methods. This research involves an examination of historical operational losses data spanning from January 2019 to December 2022 to calculate the Operational Value at Risk at different percentiles. The OpVar, a key metric in this study, is determined to be Rp17,68Billion at a 95% percentile and Rp41,4Billion at a 99% percentile. These figures represent the estimated financial loss that EPC company may face due to operational risk with a higher percentile may indicate more precise. These results were declared valid through backtesting. From these points, the research emphasizes that the signifance of understanding and learning from historical data, will enable EPC companies to understand potential risks and manage risks through risk mitigation strategies in the complexity of EPC business environment.